2016
DOI: 10.1515/jpem-2014-0479
|View full text |Cite
|
Sign up to set email alerts
|

Transient congenital hypothyroidism caused by compound heterozygous mutations affecting the NADPH-oxidase domain of DUOX2

Abstract: Here, we describe three cases of loss-of-function mutations in the nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase (NOX) domain of dual oxidase 2 (DUOX2) occurring along with concurrent missense mutations in thyroid peroxidase (TPO), leading to transient congenital hypothyroidism (CH). Three Japanese boys with nonconsanguineous parents were diagnosed with CH during their neonatal screenings. All patients presented with moderate-to-severe neonatal hypothyroidism and were diagnosed with transient CH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…A recent report revealed that the combination of biallelic mutation in DUOX2 with the monoallelic mutation in a different thyroid hormone-generating enzyme might cause CH. (35). However in some cases, the combination of biallelic mutation in DUOX2 with the monoallelic mutation in a Supply of H 2 O 2 production Figure 2 The proposed mechanism underlying the development of transient CH due to DUOX2 defects.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report revealed that the combination of biallelic mutation in DUOX2 with the monoallelic mutation in a different thyroid hormone-generating enzyme might cause CH. (35). However in some cases, the combination of biallelic mutation in DUOX2 with the monoallelic mutation in a Supply of H 2 O 2 production Figure 2 The proposed mechanism underlying the development of transient CH due to DUOX2 defects.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of multiple genetic alterations in the DUOX2 gene such as tri-allelic mutations has been associated with an increase in the severity of the disease [106,112,113]. In addition, increasing number of clinical case studies report DUOX2 pathogenic variants concomitant with genetic alterations in other genes involved in TH synthesis including TG [125,127], TSHr [102,109,118,132], TPO [133], Pendrin [115], and DUOXA2 [107,123]. Additional studies would clarify their functional relevance in the evolution of the pathology.…”
Section: Duox Functional Characterization In Heterologous Cell Systemsmentioning
confidence: 99%
“…Moreover, as the basal activity of the oxidase is very low, agents increasing the intracellular Ca 2+ concentration must be added in the assay. The calcium ionophore ionomycin [55,106,110,116,[133][134][135] and the Ca 2+ -ATPase inhibitor thapsigargin [104,111] have been successfully used in different assays. The cell type could also modify the final outcome of the assay in terms of activity or maturation of the protein.…”
Section: Duox Functional Characterization In Heterologous Cell Systemsmentioning
confidence: 99%
“…This phenotypic or genetic heterogeneity suggests that mono-and polygenic factors and environmental modulators have roles in the determination of disease severity (4,5). Some cases have oligogenic mutations apart from single-gene mutations and demonstrate heterogeneous phenotypes to those carrying monogenic mutations (15)(16)(17). These cases may not be inherited in a monogenic manner; that is, a digenic or oligogenic inheritance may be considered, or mutations may occur, acting as a genetic modifiers (18,19).…”
Section: Introductionmentioning
confidence: 99%